Importance of Land, family and culture for a good life: Remote Aboriginal people with disability and carers. Issue 4 (23rd December 2019) - Dew, Angela; Barton, Rebecca; Gilroy, John; Ryall, Lee; Lincoln, Michelle; Jensen, Heather; Flood, Vicki; Taylor, Kerry; McCrae, Kim
Abstract: Worldwide health and social outcomes of Indigenous people are poorer than those of non‐Indigenous. In Australia, the Indigenous population experience disability at more than twice the rate of the non‐Indigenous population, and a quarter live in geographically remote areas. The challenges associated with accessing services and supports in remote communities can impact on a good life for Aboriginal people with disability. Interviews were conducted with Aboriginal people (An angu) with disability and family carers from remote Central Australian communities and service workers. Thematic data analysis determined factors An angu viewed as essential to living a good life: connection to their Lands, being with family and engaging in cultural activities. Workers' support for a good life involves "Proper Way" help and an understanding of An angu culture. Three culturally relevant strengths‐based concepts are important in supporting An angu with disability to live a good life: being connected to the Lands and family, sharing together and working together.